A Double-Blinded, Randomized, Vehicle-Controlled Study of the Efficacy of Moisturizer Containing Licochalcone A, Decanediol, L-Carnitine, and Salicylic Acid for Prevention of Acne Relapse in Asian Population. (23rd October 2020) - Kulthanan, Kanokvalai; Trakanwittayarak, Suphattra; Tuchinda, Papapit; Chularojanamontri, Leena; Limphoka, Pichaya; Varothai, Supenya
Abstract : Many topical agents are available for treating the acute phase of acne; however, few agents have been proven beneficial during the maintenance phase. Objective. To evaluate the efficacy and safety of moisturizer containing licochalcone A, 1, 2-decanediol, L-carnitine, and salicylic acid during the maintenance phase of mild to moderate acne in Thai patients. Methods. One hundred and ten patients with mild to moderate acne vulgaris were initially treated with a fixed combination of adapalene 0.1%/benzoyl peroxide 2.5% gel once daily for 8 weeks. Fifty patients who achieved at least 50% reduction in lesion counts or at least a 2-grade improvement in the Investigator's Global Assessment (IGA) grade from baseline were enrolled in the maintenance phase, which was an investigator-masked, left-right comparison, randomized, controlled, intraindividual study. Moisturizers with and without the active study ingredients were applied twice a day to each side of the face, respectively, for 12 weeks. Assessments included acne lesion counts, acne severity by IGA scoring, skin bioengineering measurements, and skin tolerability as assessed by both patient and physician. Results. The treatment group had a significant reduction in the mean counts of noninflammatory, inflammatory, and total lesions compared to the vehicle group at week 12 and also between baseline and week 12. There was no significant difference in the mean scores for skin dryness, stinging/burning, or pruritus at any time point between groups. Conclusions. Moisturizer containing licochalcone A, 1, 2-decanediol, L-carnitine, and salicylic acid reduced acne lesions and prevented the development of new lesions during the maintenance phase. This trial is registered with ClinicalTrials.gov registration no. NCT04002024 .